FORMULASI DAN UJI STABILITAS FISIK FACIAL FOAM ANTI ACNE DARI MINYAK BIJI SEMANGKA (Citrullus lanatus) - Hashary, A Rufaidah; Yunus, Arifuddin Yunus; Natsir, Rahmawati (Jurnal Riset Kefarmasian Indonesia, 2025)
Facial foam is a foaming facial cleansing preparation formulated to provide a thorough cleansing effect while maintaining skin softness. This study aims to formulate and test the physical stability of facial foam containing watermelon seed oil (Citrullus lanatus seed oil) as a natural active ingredient. Watermelon seed oil is known to contain essential fatty acids and antioxidant compounds that act as anti-acne agents. Formulation is done with the selection of surfactants and additives that support the formation of abundant foam, pH balance, and a comfortable texture to use. The evaluation of the preparation includes organoleptic test, pH, homogeneity, foam height and stability, wetting power, and leaching power to ensure the physical stability and quality of the product. The results showed that the formulated facial foam has good physical characteristics, pH in accordance with the facial skin, and stable. Facial foam based on watermelon seed oil has the potential to be a natural facial cleansing product that is effective and safe to use.